Lithium ion battery electrolyte containing cyano sulfonamide compound and lithium ion secondary battery
By using electrolyte of cyanosulfonamide compound in lithium-ion batteries, a low-impedance SEI film is formed and the dissolution of transition metal ions is suppressed, which solves the problem of degradation of the cycle performance of lithium-ion batteries under high voltage, and significantly improves the cycle of the battery and storage performance.
Patent Information
- Application Number
- CN202411622063.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2024-12-17
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The cycling performance of lithium-ion batteries at high voltages decreases, and the instability of the positive electrode material leads to the dissolution of transition metal and the decomposition of electrolytes, which increases the internal resistance of the battery and affects the battery life and storage performance.
Using a lithium-ion battery electrolyte containing cyanosulfonamide compound, a low-impedance SEI film is formed through the sulfonyl structure of cyanosulfonamide compound, which inhibits the contact and side reaction of the positive and negative electrodes, and reduces the transition metal ions by complexing. It dissolves, improving the cycling performance of the battery.
It effectively improves the cycling performance of lithium-ion batteries at high voltages, reduces the dissolution of transition metal ions and the oxidation of electrolytes, and extends the cycle life and storage performance of the battery.
Smart Images

Figure SMS_26 
Figure SMS_27 
Figure QLYQS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of battery materials, and in particular relates to a lithium ion battery electrolyte and a lithium ion secondary battery containing a cyanosulfonamide compound. Background Art
[0002] Lithium-ion batteries have become an ideal power source for portable devices, power systems and energy storage due to their advantages such as light weight, small size, low self-discharge, no pollution, and no memory effect. In recent years, on the one hand, mobile electronic devices, especially smart phones, have developed towards lighter and thinner, and on the other hand, electric vehicles have also developed towards longer mileage, all of which have put forward higher requirements on the energy density of lithium-ion batteries.
[0003] At present, the most direct and effective way to improve the energy density of batteries is to use high-voltage positive electrode active materials. For example, the Chinese patent with authorization announcement number CN102891307B discloses a high-voltage lithium-ion battery composite positive electrode material and a lithium-ion battery. The coating layer can exert an effective gram capacity and discharge voltage platform under high voltage, thereby improving the energy density of the battery. The coating layer enhances the structural stability of the matrix material, effectively inhibits the dissolution of Mn in the material during the cycle, and reduces the oxidation of the positive electrode material electrolyte.
[0004] However, there are some risks in the use of high-voltage positive electrode active materials, such as the instability of the positive electrode material itself, some side reactions, and the dissolution of transition metals. At the same time, the positive electrode material catalyzes the decomposition of the electrolyte and produces a large amount of gas. As the battery charge and discharge cycle proceeds, the internal resistance of the battery gradually increases, resulting in a decrease in the cycle performance of the lithium-ion battery or even failure. Therefore, it is necessary to develop a high-voltage resistant lithium-ion battery electrolyte so that the lithium-ion battery containing the electrolyte has excellent cycle performance under high voltage. Summary of the invention
[0005] The purpose of the present invention is to provide a lithium ion battery electrolyte and a lithium ion secondary battery containing a cyanosulfonamide compound, which can effectively improve the cycle performance of the lithium ion battery under high voltage.
[0006] The technical solution adopted by the present invention is as follows: A lithium ion battery electrolyte and a lithium ion secondary battery containing a cyanosulfonamide compound, comprising an organic solvent, a lithium salt and an additive, wherein the additive comprises at least one of fluoroethylene carbonate, vinyl sulfate, vinyl sulfite, 1,3-propane sultone, 1,3-propene sultone, vinylene carbonate, and vinyl ethylene carbonate and a cyanosulfonamide compound.
[0007] Furthermore, the cyanosulfonamide compound has a structure shown in formula (1): Formula (1) In formula (I), R1 includes any one of -F, -CF3, cyclopentane, cyclohexane, fluorinated phenyl, unsaturated cycloalkyl, and cycloalkyl containing unsaturated branches; R2 includes any one of C1-6 alkyl; R3 includes any one of C1-6 terminal alkenyl and C1-6 terminal cyano.
[0008] Furthermore, the cyanosulfonamide compound has a structure represented by any one of the structural formulas (2) to (12): Formula (2) Formula (3) Formula (4) Formula (5) Formula (6) Formula (7) Formula (8) Formula (9) Formula (10) Formula (11) Formula (12).
[0009] Furthermore, the content of the cyanosulfonamide compound is 0.1-10%, and the concentration of the lithium salt in the electrolyte is 0.5-1.5 mol / L.
[0010] Furthermore, the content of the cyanosulfonamide compound is 0.5-5%, and the content of the lithium salt is 7-15%.
[0011] Further, the organic solvent includes at least one of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl acetate, ethyl acetate, propyl acetate, butyl acetate, propyl propionate, ethyl propionate, and butyl propionate; The lithium salt includes at least one of LiPF6, LiClO4, LiBOB, LiBF4, LiPF2O2, LiODFB, LiTFSI, LiFSI and LiC(CF3SO2)3.
[0012] Furthermore, the organic solvent is a mixture of ethylene carbonate and ethyl methyl carbonate, and the content of ethylene carbonate is 15-30%.
[0013] A lithium ion secondary battery comprises a battery core, a battery shell and the above-mentioned electrolyte.
[0014] The battery cell comprises a positive electrode sheet, a negative electrode sheet and a separator; The positive electrode sheet comprises a positive electrode current collector and a positive electrode material coated on the surface of the positive electrode current collector, wherein the positive electrode material comprises a positive electrode active material, a positive electrode conductive agent, and a positive electrode binder; In the positive electrode material, the content of the positive electrode active material is 90-98%, the content of the positive electrode conductor is 0.1-9%, and the content of the positive electrode binder is 0.5-5%; The negative electrode sheet comprises a negative electrode current collector and a negative electrode material coated on the surface of the negative electrode current collector, wherein the negative electrode material comprises a negative electrode active material, a negative electrode conductive agent, a negative electrode binder, and a thickener; In the negative electrode material, the content of the negative electrode active material is 91-98%, the content of the negative electrode conductor is 0-8%, the content of the negative electrode binder is 0.5-5%, and the content of the thickener is 0.5-5%.
[0015] A method for preparing a lithium ion secondary battery, the method comprising the following steps: The positive electrode sheet, the negative electrode sheet and the separator are stacked to form a battery cell; The battery cell is packaged with a polymer, vacuum-baked at 85° C. for 24 hours, injected with an electrolyte, and subjected to an infiltration and formation process to obtain a lithium-ion secondary battery.
[0016] The technical effects achieved by the present invention are: The lithium ion battery electrolyte containing a cyanosulfonamide compound of the present invention contains a sulfonyl structure, which can form a low-impedance sulfate ester or sulfate SEI film at the positive electrode / negative electrode, and can effectively reduce the contact between the electrolyte and the positive and negative electrode plates and the occurrence of side reactions; F forms an inner layer LiF, and the left cyclic / unsaturated functional group can preferentially undergo oxidation or reduction reaction at the positive electrode / negative electrode to form a protective film; the cyano group can complex the positive electrode transition metal and effectively inhibit the dissolution of the transition metal ion; thereby reducing the dissolution of the transition metal ion, the oxidation of the electrolyte, the self-discharge and the occurrence of other side reactions under high voltage, thereby improving the cycle performance, capacity retention and the like; by using a specific type of electrolyte additive, an organic solvent and a lithium salt, the cycle performance of the lithium ion battery under high voltage can be effectively improved, and the lithium ion battery prepared by using the lithium ion battery electrolyte of the present invention has excellent cycle performance under high voltage. DETAILED DESCRIPTION
[0017] In order to make the purpose and advantages of the present invention more clearly understood, the present invention is specifically described below in conjunction with embodiments. It should be understood that the following text is only used to describe one or several specific embodiments of the present invention, and does not strictly limit the scope of protection of the specific claims of the present invention. Example 1
[0018] A lithium-ion battery electrolyte containing a cyanosulfonamide compound comprises an organic solvent, a lithium salt and an additive, wherein the additive comprises at least one of fluoroethylene carbonate, vinyl sulfate, vinyl sulfite, 1,3-propane sultone, 1,3-propene sultone, vinylene carbonate, and vinyl ethylene carbonate and a cyanosulfonamide compound.
[0019] The cyanosulfonamide compound has the structure shown in formula (1): Formula (1) In formula (I), R1 includes any one of -F, -CF3, cyclopentane, cyclohexane, fluorinated phenyl, unsaturated cycloalkyl, and cycloalkyl containing unsaturated branches, wherein the fluorinated phenyl is preferably p-fluorophenyl; R2 includes any one of C1-6 alkyl; R3 includes any one of C1-6 terminal alkenyl and C1-6 terminal cyano.
[0020] The cyanosulfonamide compound has a structure represented by any one of the structural formulas (2) to (12): Formula (2) Formula (3) Formula (4) Formula (5) Formula (6) Formula (7) Formula (8) Formula (9) Formula (10) Formula (11) Formula (12) Moreover, based on the total mass of the electrolyte, the content of the cyanosulfonamide compound is 0.1-10%, that is, the mass of the cyanosulfonamide compound: the total mass of the electrolyte is 0.1-10:100, and the content of the cyanosulfonamide compound is preferably 0.5-5%.
[0021] The organic solvent includes at least one of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl acetate, ethyl acetate, propyl acetate, butyl acetate, propyl propionate, ethyl propionate and butyl propionate, and the organic solvent is a mixture of ethylene carbonate and ethyl methyl carbonate. Based on the total mass of the organic solvent, the content of ethylene carbonate is 15-30%; that is, the ratio of ethylene carbonate to ethyl methyl carbonate is 15-30:70-85.
[0022] Among them, the lithium salt includes at least one of LiPF6, LiClO4, LiBOB, LiBF4, LiPF2O2, LiODFB, LiTFSI, LiFSI and LiC(CF3SO2)3, and the concentration of the lithium salt in the electrolyte is 0.5-1.5 mol / L, preferably 0.8-1.3 mol / L, that is, based on the total mass of the electrolyte, the content of lithium salt in the electrolyte is 7-15%.
[0023] The electrolyte in this embodiment contains a sulfonyl structure, which can form a low-impedance sulfate or sulfate SEI film at the positive electrode / negative electrode, which can effectively reduce the contact between the electrolyte and the positive and negative electrode plates and the occurrence of side reactions; F forms an inner layer of LiF, and the left cyclic / unsaturated functional group can preferentially undergo oxidation or reduction reactions at the positive electrode / negative electrode to form a protective film; the cyanide group can complex the positive electrode transition metal and effectively inhibit the dissolution of transition metal ions; thereby reducing the dissolution of transition metal ions, oxidation of the electrolyte, self-discharge and other side reactions under high voltage, thereby improving the cycle, capacity retention and other performance. By using specific types of electrolyte additives, organic solvents and lithium salts, the cycle performance of lithium-ion batteries under high voltage can be effectively improved. Example 2
[0024] This embodiment discloses a lithium-ion secondary battery based on the first embodiment. The lithium-ion secondary battery includes a battery cell, a battery casing and the electrolyte in the first embodiment.
[0025] Among them, the battery cell includes a positive electrode sheet, a negative electrode sheet and a separator.
[0026] The positive electrode sheet includes a positive electrode current collector and a positive electrode material coated on the surface of the positive electrode current collector. The positive electrode material includes a positive electrode active material, a positive electrode conductive agent, and a positive electrode binder.
[0027] In the positive electrode material, based on the total mass of the positive electrode active material, the positive electrode conductor and the positive electrode binder, the content of the positive electrode active material is 90-98%, the content of the positive electrode conductor is 0.1-9%, and the content of the positive electrode binder is 0.5-5%.
[0028] The negative electrode sheet includes a negative electrode current collector and a negative electrode material coated on the surface of the negative electrode current collector. The negative electrode material includes a negative electrode active material, a negative electrode conductive agent, a negative electrode binder, and a thickener.
[0029] In the negative electrode material, based on the total mass of the negative electrode active material, the negative electrode conductor, the negative electrode binder and the thickener, the content of the negative electrode active material is 91-98%, the content of the negative electrode conductor is 0-8%, the content of the negative electrode binder is 0.5-5%, and the content of the thickener is 0.5-5%.
[0030] There is no particular restriction on the types of positive and negative electrode active materials, conductive agents, and binders, and they may be conventional materials in the art. For example, the positive electrode active material may be any one of lithium cobalt oxide, ternary materials, and lithium iron phosphate; the negative electrode active material may be any one of graphite, silicon-based materials, and lithium titanate; the positive electrode conductive agent and the negative electrode conductive agent may be any one of carbon black, conductive graphite, carbon nanotubes, and graphene; and the positive electrode binder and the negative electrode binder may be any one of polyvinylidene fluoride and polyacrylic acid. Example 3
[0031] This embodiment discloses a method for preparing a lithium ion secondary battery based on embodiment 2. The method for preparing a lithium ion secondary battery comprises the following steps: Step (1) Preparation of positive electrode of lithium-ion battery: The positive electrode active material nickel cobalt manganese lithium (LiNi 0.5 Co 0.2 Mn 0.3 O2), conductive agent (super-P), and binder polyvinylidene fluoride (PVDF) are dissolved in solvent N-methylpyrrolidone (NMP), mixed evenly to form positive electrode slurry, and the positive electrode slurry is evenly coated on aluminum foil with a coating surface density of 0.040g / cm 2 , then dried at 130°C, cold pressed and punched, then dried at 85°C under vacuum conditions for 24 hours, and the tabs were welded to make a lithium-ion battery positive electrode sheet that meets the requirements.
[0032] Step (2) Preparation of negative electrode sheet of lithium-ion battery: Artificial graphite, a conductive agent (super-P), a thickener (sodium carboxymethyl cellulose (CMC), and a binder (styrene-butadiene rubber (SBR)) of a negative electrode active material with a mass ratio of 95:1:1.5:2.5 were dissolved in deionized water and mixed evenly to form a negative electrode slurry. The negative electrode slurry was evenly coated on a copper foil with a coating surface density of 0.024 g / cm 2 , then dried at 100°C, cold pressed and punched, then dried at 110°C under vacuum conditions for 24 hours, and the tabs were welded to make a lithium-ion battery negative electrode sheet that meets the requirements.
[0033] Step (3) Preparation method of lithium ion battery electrolyte: LiPF6 was used as lithium salt with a lithium salt concentration of 1 mol / L, and a mixture of ethylene carbonate (EC) and ethyl methyl carbonate (EMC) was used as an organic solvent, wherein the weight ratio of EC:EMC:DMC was 3:6:1. 2% fluoroethylene carbonate (FEC), 1% 1,3-propane sultone (PS), and 1% , and obtain an electrolyte.
[0034] Step (4) Preparation method of lithium ion secondary battery: The positive electrode sheet, negative electrode sheet and separator prepared above were stacked to form a soft-pack battery cell, packaged with a polymer, vacuum-baked at 85° C. for 24 h, injected with the electrolyte in Example 1, and manufactured into a lithium-ion battery with a capacity of 2000 mAh after processes such as infiltration and formation.
[0035] The above electrolyte is preferably an electrolyte prepared according to a method for preparing a lithium ion battery electrolyte.
[0036] The conventional formation of the first charge was carried out according to the following steps: charging to 3.6V with a constant current of 0.1C, charging to 3.95V with a constant current of 0.2C, vacuum sealing for the second time, and then charging to 4.35V with a constant current of 0.2C. After standing at room temperature for 24h, discharging to 3.0V with a constant current of 0.2C, a 4.35V LiNi 0.5 Co 0.2 Mn 0.3 O2 / artificial graphite lithium-ion battery. Example 4
[0037] This embodiment adopts the same method as that of Embodiment 1 to prepare the positive electrode, negative electrode, electrolyte and lithium ion battery of the lithium ion battery, except that in the preparation of the lithium ion battery electrolyte in step (3), the structure of the cyanosulfonamide compound used is different, as shown in Table 1.
[0038] In order to further illustrate the prepared lithium ion battery, the present technical solution sets up a comparative example, in which the positive electrode, negative electrode, electrolyte and lithium ion secondary battery of the lithium ion battery are prepared by the same method as in Example 3, except that in the preparation of the lithium ion battery electrolyte in step (3), no silane sulfonamide compound is added, and the rest is the same as in Example 3, as shown in Table 1.
[0039] Table 1
[0040] The first coulombic efficiency and cycle performance of the lithium ion secondary battery prepared above were tested, and the test results are shown in Table 2. The coulombic efficiency, cycle performance and high temperature storage performance were measured by the following methods: Coulomb efficiency (%) = (discharge capacity / charge capacity) × 100%.
[0041] (1) High temperature cycle performance test of lithium-ion batteries At 45°C, the lithium-ion battery is charged to 4.35V at a constant current of 1C, then charged to 0.05V at a constant voltage of 4.35V, and then discharged to 2.75V at a constant current of 1C as a cycle. The discharge capacity this time is the discharge capacity of the first cycle. Taking the discharge capacity of the first cycle as 100%, the lithium-ion battery is subjected to 500 cycle charge / discharge tests according to the above method, and the discharge capacity of the 500th cycle is detected.
[0042] Capacity retention rate after 500 cycles at 45°C (%) = 500th cycle discharge capacity / first cycle discharge capacity × 100%.
[0043] (2) Lithium-ion battery high temperature storage performance test At room temperature, the lithium-ion battery was charged to 4.35V at a constant current of 1C, then charged to 0.05C at a constant voltage of 4.35V, and the charging capacity C0 was recorded. Then, it was discharged to 2.75V at a constant current of 1C, and the discharge capacity D0 was recorded. After the battery was fully charged according to the above charging method, it was stored at 70°C for 30 days. After the storage, it was discharged to 2.75V at a constant current of 1C, and the discharge capacity D1 was recorded. Then, it was charged to 4.35V at a constant current of 1C, and then charged to 0.05C at a constant voltage of 4.35V, and the charging capacity C1 was recorded.
[0044] Capacity retention rate (%) = (D1 / D0) × 100%.
[0045] Capacity recovery rate (%) = (C1 / C0) × 100%.
[0046] Table 2
[0047] It can be seen from the above results that the coulombic efficiency of the lithium ion secondary battery prepared by the lithium ion battery electrolyte of the present invention is 93%, and the capacity retention rate of 500 cycles at 1C at 45°C is 93%; while the coulombic efficiency of the lithium ion secondary battery of the prior art is 85%, and the capacity retention rate of 500 cycles at 1C at 45°C is 85%.
[0048] At the same time, the high-temperature storage performance of the lithium-ion secondary battery prepared as above was also tested. The lithium-ion secondary battery prepared by the lithium-ion battery electrolyte of the present invention was placed in an environment of 60°C for 7 days, and the capacity retention rate could reach 83.51%, and the capacity recovery rate could reach 88.80%. The capacity retention rate of the lithium-ion secondary battery of Comparative Example 1 was 75.80% and the capacity recovery rate was 78.60% when placed at 60°C for 7 days.
[0049] It can be seen from the above that the lithium ion battery prepared by using the lithium ion battery electrolyte of the present invention has excellent cycle performance at high voltage.
[0050] The above are only preferred embodiments of the present invention. It should be noted that, for those skilled in the art, several improvements and modifications can be made without departing from the principles of the present invention, and these improvements and modifications should also be considered as the protection scope of the present invention. The structures, devices and operating methods not specifically described and explained in the present invention shall be implemented according to conventional means in the art unless otherwise specified and limited.
Claims
1. A lithium ion battery electrolyte containing a cyanosulfonamide compound, characterized in that: The invention comprises an organic solvent, a lithium salt and an additive, wherein the additive comprises at least one of fluoroethylene carbonate, vinyl sulfate, vinyl sulfite, 1,3-propane sultone, 1,3-propene sultone, vinylene carbonate, vinyl ethylene carbonate and a cyanosulfonamide compound.
2. The lithium ion battery electrolyte containing a cyanosulfonamide compound according to claim 1, characterized in that: The cyanosulfonamide compound has a structure shown in formula (1): Formula (1) In formula (I), R1 includes any one of -F, -CF3, cyclopentane, cyclohexane, fluorinated phenyl, unsaturated cycloalkyl, and cycloalkyl containing unsaturated branches; R2 includes any one of C1-6 alkyl; R3 includes any one of C1-6 terminal alkenyl and C1-6 terminal cyano.
3. The lithium ion battery electrolyte containing a cyanosulfonamide compound according to claim 1, characterized in that: The cyanosulfonamide compound has a structure represented by any one of the structural formulas (2) to (12): Formula (2) Formula (3) Formula (4) Formula (5) Formula (6) Formula (7) Formula (8) Formula (9) Formula (10) Formula (11) Formula (12).
4. The lithium ion battery electrolyte containing a cyanosulfonamide compound according to claim 1, characterized in that: The content of the cyanosulfonamide compound is 0.1-10%, and the content of the lithium salt in the electrolyte is 7-15%.
5. A lithium ion battery electrolyte containing a cyanosulfonamide compound according to claim 4, characterized in that: The content of the cyanosulfonamide compound is 0.5-5%.
6. The lithium ion battery electrolyte containing a cyanosulfonamide compound according to claim 1, characterized in that: The organic solvent comprises at least one of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl acetate, ethyl acetate, propyl acetate, butyl acetate, propyl propionate, ethyl propionate, and butyl propionate; The lithium salt includes at least one of LiPF6, LiClO4, LiBOB, LiBF4, LiPF2O2, LiODFB, LiTFSI, LiFSI and LiC(CF3SO2)3.
7. A lithium ion battery electrolyte containing a cyanosulfonamide compound according to claim 6, characterized in that: The organic solvent is a mixture of ethylene carbonate and ethyl methyl carbonate, and the content of the ethylene carbonate is 15-30%.
8. A lithium ion secondary battery, characterized in that: The invention comprises a battery core, a battery casing and the electrolyte according to any one of claims 1 to 7.
9. A lithium ion secondary battery according to claim 8, characterized in that: The battery cell comprises a positive electrode sheet, a negative electrode sheet and a separator; The positive electrode sheet comprises a positive electrode current collector and a positive electrode material coated on the surface of the positive electrode current collector, wherein the positive electrode material comprises a positive electrode active material, a positive electrode conductive agent, and a positive electrode binder; In the positive electrode material, the content of the positive electrode active material is 90-98%, the content of the positive electrode conductor is 0.1-9%, and the content of the positive electrode binder is 0.5-5%; The negative electrode sheet comprises a negative electrode current collector and a negative electrode material coated on the surface of the negative electrode current collector, wherein the negative electrode material comprises a negative electrode active material, a negative electrode conductive agent, a negative electrode binder, and a thickener; In the negative electrode material, the content of the negative electrode active material is 91-98%, the content of the negative electrode conductor is 0-8%, the content of the negative electrode binder is 0.5-5%, and the content of the thickener is 0.5-5%.
10. A method for preparing a lithium ion secondary battery, for preparing the lithium ion secondary battery as claimed in claim 8, characterized in that: The preparation method comprises the following steps: The positive electrode sheet, the negative electrode sheet and the separator are stacked to form a battery cell; The battery cell is packaged with a polymer, vacuum-baked at 85° C. for 24 hours, injected with an electrolyte, and subjected to an infiltration and formation process to obtain a lithium-ion secondary battery.
Citation Information
Patent Citations
High-voltage electrolyte and lithium ion battery containing same
CN111092264A
Lithium ion battery electrolyte containing silane-based sulfonamide compound, and lithium ion secondary battery
CN112928328A
Lithium ion battery
CN113410510A
Nonaqueous electrolytic solution, and nonaqueous electrolytic battery using the same
JP2014186957A
Method for depositing boron containing silicon germanium layers
KR1020210156219A
Cited By
Electrolyte additive and preparation method therefor, secondary battery, and electronic device
WO2025252004A1
